2011
DOI: 10.1074/jbc.m111.268201
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Fates of Paused Ribosomes during Translation Termination

Abstract: The bacterial tmRNA⅐SmpB system facilitates recycling of stalled translational complexes in a process termed "ribosome rescue." During ribosome rescue, the nascent chain is tagged with the tmRNA-encoded ssrA peptide, which targets the tagged polypeptide for degradation. Translational pausing also induces a variety of recoding events such as frameshifts, ribosome hops, and stop codon readthrough. To examine the interplay between recoding and ribosome rescue, we determined the various fates of ribosomes that pau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…Ribosomes stall due to a variety of translational impediments, including structures in the mRNA (Doma and Parker 2006), the absence of stop codons van Hoof et al 2002), the presence of inhibitory amino acid combinations (Gutierrez et al 2013;Woolstenhulme et al 2013), or the presence of inhibitory codon combinations (Letzring et al 2010;Seidman et al 2011). Such sequences may substantially impact downstream translation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ribosomes stall due to a variety of translational impediments, including structures in the mRNA (Doma and Parker 2006), the absence of stop codons van Hoof et al 2002), the presence of inhibitory amino acid combinations (Gutierrez et al 2013;Woolstenhulme et al 2013), or the presence of inhibitory codon combinations (Letzring et al 2010;Seidman et al 2011). Such sequences may substantially impact downstream translation.…”
Section: Introductionmentioning
confidence: 99%
“…In bacteria, such as Escherichia coli, stalled ribosomes are sometimes rescued by the trans-acting tmRNA·SmpB system (Moore and Sauer 2007), but may also undergo translational recoding, in particular +1 frameshifting (Seidman et al 2011). Errors in which ribosomes switch reading frames generally occur at extremely low rates, 3 × 10 −5 (Kurland 1992), and are almost certain to result in a nonfunctional polypeptide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies demonstrated that L9 also influences frameshifting at codon repeats and stop codons (12,(14)(15)(16). More recently, L9 deletion strains were shown to read through stop codons more frequently (out of frame) and encounter the 3= ends of their engaged mRNAs, which then invokes ribosome rescue systems (8). Thus, at least one role for L9 is in maintaining translation fidelity, but nothing is known about the mechanism for this activity.…”
mentioning
confidence: 99%
“…Interestingly, some very highly conserved ribosomal proteins can be deleted from bacteria without inducing appreciable growth phenotypes, which obfuscates determination of their molecular functions (2,6). The bacterium-specific ribosomal protein L9 is an example of this nonessential class: it possesses a conserved secondary and tertiary architecture and contains several invariant amino acids, yet deletion strains grow well (7)(8)(9). From the perspective that all highly conserved factors serve as windows to important cellular processes, we reasoned that a deeper understanding of L9 would help connect this enigmatic ribosomal protein to basic bacterial physiology.…”
mentioning
confidence: 99%